The Effect of Inflation, the Rupiah Exchange Rate, the BI Interest Rate, and Sales Growth on Stock Prices in the Jakarta Islamic Index (JII) 2020-2024 - Kadek Kurnia Ningsih; Endang Asliana; Artie Arditha Rachman (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to analyze the influence of macroeconomic factors namely inflation, the rupiah exchange rate, and the BI interest rate and a micro-fundamental factor, sales growth, on stock prices of companies listed in the Jakarta Islamic Index (JII) during the 2020–2024 period. Using a quantitative method and SPSS 25, the research data were selected through purposive sampling. The test results indicate that inflation has a significant effect on stock prices, whereas the rupiah exchange rate, BI interest rate, and sales growth do not show a significant partial effect. However, the four variables are proven to have a simultaneous effect on JII stock price movements. These findings emphasize that stock price dynamics are influenced not only by macroeconomic conditions but also by the internal performance of companies. Therefore, a comprehensive understanding of both external factors and company fundamentals is crucial for investors, firms, and policymakers in responding to capital market volatility in the post-pandemic period.